Characterization of the rear wake of a SUV with extensions and without extensions. (August 2017) - Sebben, Simone; Sterken, Lennert; Wölken, Thies
Passenger vehicles are considered to be bluff bodies, and therefore their total aerodynamic resistance is dominated by the pressure drag, which is basically the difference between the stagnation pressure at the front and the pressure at the base. In particular, the base wake of a vehicle has a significant influence on the total drag, and the ways to reduce and to control the drag have been the subject of numerous investigations. The present work focuses on the identification and analysis of unsteady-flow structures acting on the base wake of a sport utility vehicle with rear-end extensions and without rear-end extensions. Tapered extensions have proved to be an effective way to reduce the drag since they act as a truncated boat-tailing device which improves the pressure recovery zone and reduces the wake size. In this investigation, wind tunnel experiments and computational fluid dynamics were used to study the forces acting on the vehicle and the non-stationary behaviour of the rear wake flow. For analysis of the unsteady base pressures, a data-structure-sensitive filtering approach based on empirical mode decomposition in combination with fast Fourier transform and proper orthogonal decomposition was used. The numerical results and the experimental results complement each other well, and both revealed an antisymmetric mode in the transverse plane related to a flapping of the wake at a Strouhal number of around 0.23. Furthermore, a pumping effect, which is a main contributor to the drag, was observed at Strouhal values of between 0.04 and 0.07. This is in good agreement with the results from the research on more simplified model shapes. The rear extensions proved to be a productive way to reduce the drag coefficient and the magnitude of the wake flapping for the yaw angles investigated.